STABILIZATION OF LOCAL SOIL WITH CEMENT PLUS DIFA STABILIZER ADDITIVE FOR SUBGRADE IMPROVEMENT AND PROTECTION CASE STUDY IN TANJUNGPINANG CITY, RIAU PROVINCE. - Syahminan, Mohamad; Ramadhani, Niko (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2025)
The high Plasticity Index values of subgrade conditions will affect compacting process and difficulty to obtain a minimum density standard, this is a serious problem on the second line of Dompak bridges III street to the port of Roro Dompak city of Tanjung Pinang. The purposes study to analyze of the soil density values and the free pressure strong values (UCS) of the cement soil plus additive Difa soil stabilizer. The research was conducted using comprehensive qualitative methods in the Civil Engineering Laboratory, Faculty of Engineering, Islamic University of Riau. The composition 1 kg Difa SS for 1 M3 surface dry soil weight with cement variations 8%, 10%, 12%, 14%. Analysis carried out with Proctor Standard and UCS test, the result of original soil density values of 1.323 kg/m3 and soil cement mixture 8% at 1.460 kg/m3, 10% at 1.470 kg/m3, 12% at 1,470 kg/m3 and 14% at 1.500 kg/m3. The UCS condition values soaked for soil mixture of 8% cement plus 1kg/ m3 additive obtained 214,32 kN/m2, 10% at 527,57 kN/m2, 12% at 989,19 kN/m2, 14% at 1.005,68 kN/m2. The UCS value of unsoaked condition of the original soil was obtained at 138.64 kN/m2, the composition of cement mixture at 8% plus 1 kg/m3 Difa SS obtained the UCS values at 735.27 kN/m2, 10% at 942.23 kN/m2, 12% at 1.023.93 kN/m2, 14% at 1.813,51 kN/m2.